Species Composition, Relative Abundance, and Habitat Association of Avifauna in Zegie Peninsula Forest Patches and Associated Wetlands, Bahir Dar, Ethiopia - Mola, Misganaw; Ejigu, Dessalegn; Yitayih, Yibelu (International Journal of Zoology, 2021)
Introduction. Ethiopia is one of the most avifauna rich countries in Africa. Avifaunal surveys are required to inform conservation decisions and enhance land management for biodiversity. Avifaunal surveys from Ethiopia are lacking. This study examines species composition, relative abundance, and habitat association of avian fauna in Zegie Peninsula forest patches and associated wetlands from surveys carried out from August 2018 to March 2019, covering both the wet and dry seasons. Data Collection. Forest, shrub, lakeshore, and wetland habitats were identified as ecologically relevant habitats in the study area for data collection. Data were collected using point count and line transect methods, for 24 days in total for both seasons in the morning and afternoon. Results. A total of 96 species of birds were identified during the whole study period. Out of the total, 40 species were observed during the wet season, 13 during dry and 43 species in both seasons. There was significant variation of species distribution among habitats. During the wet season, the highest species diversity was recorded in the wetland habitat followed by forest habitat. During the dry season, avian diversity was the highest in the lakeshore followed by wetlands. The highest evenness was observed in the shrubland during both the wet and dry seasons. During the wet season, the highest species similarity was recorded between wetland and lakeshore habitats, and during the dry season, the highest species similarity was recorded between forest and shrub habitats. Based on encounter rate data, 64 (66.66%) of the avian species were uncommon. Conclusions. Compared to previous studies conducted in the study area, species diversity was lower. This might be due to various anthropogenic activities such as deforestation of trees for timber and cutting trees for firewood. Therefore, awareness creation should be given to the local community to reduce habitat destruction due to various human-induced factors.